Developing and Validating Deep Learning-Based Tools for Higher-Order Thinking Skills in Indonesian Elementary Schools - Chotimah, Umi; Maharani, Siti Dewi; Jaenudin, Riswan (Edukasi, 2025)
Deep learning–based approaches have been implemented across various school subjects, such as mathematics, social studies, and literacy; however, their application in Pancasila Education remains limited, despite the subject’s strategic role in fostering students’ character development and national values. This study aims to design and validate an innovative deep learning–based instructional tool to enhance higher-order thinking skills in Indonesian elementary schools. Employing a development research design, the study was conducted in three stages: (1) a preliminary investigation to identify teachers’ instructional needs, (2) the design and prototyping of the learning tool, and (3) an assessment phase involving expert validation. Data were collected through questionnaires, semi-structured interviews, and expert review instruments. Six teachers from SD Islam A Kota Palembang participated in the needs analysis phase. The data were analyzed descriptively to determine levels of instructional need and product feasibility. The preliminary findings revealed that 84.76% of teachers recognized the importance of deep learning approaches, yet continued to rely predominantly on conventional instructional methods. Teachers also expressed strong interest in developing and implementing deep learning–based lesson plans. Expert validation results demonstrated a high level of feasibility of the developed product, with validity scores of 92% for material aspects, 96% for media aspects, and 84% for language aspects, resulting in an overall validity score of 90%, which falls into the very feasible category. These findings indicate that the deep learning–based instructional tool is valid in terms of content accuracy, media design, and language clarity, and is suitable for further classroom implementation and empirical evaluation. This study contributes to the advancement of deep learning practices in Pancasila Education and provides a foundation for strengthening students’ higher-order thinking skills through innovative instructional design.